The Structural, Magnetic and Magnetic Entropy Changes on Cofe2o4/Cofe2 Composites for Magnetic Refrigeration Application - Casagrande-Denardin, J (Elsevier B.V., 2017)
In this article, the magnetocaloric effect on thermally reduced CoFe2O4/CoFe2 composite was reported. Co-precipitated CoFe2O4 nanoparticles were thermally reduced at 500 and 800 °C for 2 h under H2 atmosphere. The reduction process resulted in different fractions of soft and hard (CoFe2O4/CoFe2) magnetic composites and the products were characterized through various procedures. The structure of CoFe2O4/CoFe2 composites was found to be cubic with an average crystallite size of 31 and 30 nm for the samples reduced at 500 and 800 °C, respectively. The stoichiometry of the composites confirmed that the percentage of soft CoFe2 magnetic phase was increased to 87% with temperature up to 800 °C for 2 h, besides showed accumulation of nanoparticles. The room temperature saturation magnetization of the CoFe2O4/CoFe2 composites increases from 184 to 190 emu/g as a consequence of high concentration of CoFe2 phase. Conversely, the sample reduced at 800 °C attained the maximum magnetization of 200 and 221 emu/g at 300 and 5 K, respectively. Field cooled (FC) and zero field cooled magnetization (ZFC) and the isothermal magnetic entropy change (ΔSm) on the CoFe2O4/CoFe2 composite (with 87% of soft CoFe2 magnetic phase) were estimated. The composite showed the interesting positive and negative magnetic entropy change (ΔSm) of 0.923 and −0.923 J/kg.K−1 near room temperature at around 310 and 290 K, respectively. © 2017 Elsevier B.V.